2011
DOI: 10.1007/s11182-011-9541-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the temperature of aluminum oxide micropowder modification with Al2O3 nanopowders on the optical properties and radiation resistance of coatings manufactured on their basis

Abstract: Influence of the temperature of aluminum oxide micropowder modification with Al 2 O 3 nanopowders in the interval 200-1000°С on the granulometric composition, diffusion reflection spectra in the wavelength range 360-2100 nm, and integral solar radiation absorption coefficient of coatings fabricated on the basis of these powders as well as on changes of these parameters upon exposure to electrons is investigated. It is demonstrated that with increase in the modification temperature, the average powder particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The prepared samples were mounted in space environment simulator "Spektr" [15]. Since the sample interaction with atmospheric oxygen after irradiation can lead to "bleaching"-a decrease in concentration of formed absorption centers of oxide reflective powders, the diffuse reflection spectra (r λ ) were registered in vacuum (in situ) after irradiation with accelerated electrons (E = 30 keV, φ = 1Á10 12 cm À2 s À1 , F = (0.5, 1, and 2) Â 10 16 cm…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prepared samples were mounted in space environment simulator "Spektr" [15]. Since the sample interaction with atmospheric oxygen after irradiation can lead to "bleaching"-a decrease in concentration of formed absorption centers of oxide reflective powders, the diffuse reflection spectra (r λ ) were registered in vacuum (in situ) after irradiation with accelerated electrons (E = 30 keV, φ = 1Á10 12 cm À2 s À1 , F = (0.5, 1, and 2) Â 10 16 cm…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical and experimental studies revealed [9][10][11][12][13][14] that the modification with nanopowders is sufficiently effective way to increase the radiation stability because they possess large specific surface and work as a "sink" for gathering electronic excitations formed during irradiation. However, the modification by nanopowders can lead to a deterioration of initial optical properties that can be induced by large absorption of native point defects in the UV and visible ranges and by absorption of chemosorbed gases in near-infrared (IR) range of spectrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation